Pelatihan Menulis dan Membaca Aksara Bali dalam Media Lontar di Museum Lontar Dukuh Penaban, Desa Adat Dukuh Penaban, Kecamatan Karangasem, Kabupaten Karangasem - I Kadek Widiantana; A.A.Diah Indrayani; Gek Diah Desi Sentana; I Nyoman Ranem; Gede Agus Budi Adnyana (Sevanam: Jurnal Pengabdian Masyarakat, 2022)
Balinese language, script, and literature are important knowledge that must be mastered by Balinese people, and Balinese ancestors have also inherited thousands of Lontar manuscripts that should be known because they are full of noble values. However, with abundant of literary heritages, only a few people have the interest and ability to write, read, or study the contents of the Lontar. Efforts are needed from an early age, in order to prepare regeneration that is able to maintain and develop the knowledge stored in the Lontar manuscripts. Based on the above background, the dedication of the Department of Religious Language and Literature Education in the 2021 fiscal year will be carried out at the Lontar Dukuh Penaban Museum, Dukuh Penaban Customary Village, Karangasem Sub-district, Karangasem Regency. The method implemented in relation to the Balinese Literacy Writing and Reading Training in Lontar Media at the Lontar Dukuh Penaban Museum, Dukuh Penaban Customary Village, Karangasem Sub-district, Karangasem Regency is a training method. At the beginning, the service team gave an explanation in advance about "Pasang Aksara Bali". With this initial explanation, it is hoped that an initial mapping can be made regarding the ability to write Balinese script for the service participants. Activities are not immediately directed to the writing of Lontar, because before the stage of writing in the Lontar, of course, the service participants must first understand the rules for writing Balinese script, which are called "Pasang Aksara Bali". The activity of writing Balinese script on lontar media only started at the 4th meeting, which began with an introduction to the tools used in writing lontar. The tools that need to be prepared include: Pangrupak, Blangko Lontar, rubber/Panyepit, Lungka-Lungka, and candlenut that has been burned. After the writing tools have been distributed, it is continued with a presentation on how to hold the Pangrupak correctly and how to form the letters in the Lontar.